2019
DOI: 10.1002/ca.23331
|View full text |Cite
|
Sign up to set email alerts
|

Regional thickness of facial skin and superficial fat: Application to the minimally invasive procedures

Abstract: Various recently introduced minimally invasive treatment modalities are now widely used for enhancing the aging face. In a special, filler is used to increase the volume of tissue, and so understanding the regional thickness and distribution of the facial superficial fat is essential for optimizing minimally invasive procedures. The aim of this study was to establish the overall facial skin and superficial fat thicknesses using a three-dimensional (3D) scanning system. From 53 adult Korean and Thai embalmed ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
29
0
3

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 51 publications
(41 citation statements)
references
References 20 publications
4
29
0
3
Order By: Relevance
“…The nose also emerged as the region with the highest overall thickness in [32]; however, differently from [31], and in contrast with the results found here, in [32], the chin had a relatively low thickness compared with the other areas. In [44] Kim et al reported that skin thickness in the cheeks was higher than in the forehead, which is again consistent with our results, although the difference did not reach statistical significance in our experiments. Interestingly, the epidermis showed the same three clusters as the dermis, but, notably, with a different ordering in terms of thickness, which in this case was: (1) lips and neck, (2) chin and nose and (3) cheeks and forehead (from thickest to thinner).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The nose also emerged as the region with the highest overall thickness in [32]; however, differently from [31], and in contrast with the results found here, in [32], the chin had a relatively low thickness compared with the other areas. In [44] Kim et al reported that skin thickness in the cheeks was higher than in the forehead, which is again consistent with our results, although the difference did not reach statistical significance in our experiments. Interestingly, the epidermis showed the same three clusters as the dermis, but, notably, with a different ordering in terms of thickness, which in this case was: (1) lips and neck, (2) chin and nose and (3) cheeks and forehead (from thickest to thinner).…”
Section: Discussionsupporting
confidence: 92%
“…It is known that the dermis accounts for most of the skin's thickness, as our results confirm. Additionally, differences in the skin thickness between the facial areas have been documented in a number of papers [30][31][32]44]. In terms of absolute values of the whole thickness, our results are in line with those reported in [32].…”
Section: Discussionsupporting
confidence: 92%
“…We compared the depth of the procerus between US images and 3D-scanning images of cadavers. Because these two methods have been validated previously [15,24,25], we used both modalities simultaneously in this study in order to increase the reliability. The depth of the procerus could be measured in 3D scanning images without any need to apply pressure; however, an important limitation was that the 3D scanning was performed on old-aged cadavers in the supine position.…”
Section: Discussionmentioning
confidence: 99%
“…For numerous diagnoses and surgical or nonoperative evaluations, 3D scanned images of the face are now popularly used (Hammond et al, ; Kim et al, ). The validity and reliability of measurements using the 3D scanning system were demonstrated in our previous study (Lee et al, ; Cong et al, ; Kim et al, ). This 3D scanning system acquires distance information based on structured light, which can be measured with an accuracy of better than 0.1 mm.…”
Section: Discussionmentioning
confidence: 68%